236 Intermittent Hypoxia: Effects on Brain Stem of Oxidative Stress and NRF2 Transcription Factor Activation in A Rat Pup Model. (October 2012) - Vento, M; Escobar, J; Kuligowski, J; Prabha, K; Martin, RJ; Cubells, E; Koroglu, O
Abstract : Background: Apnea of prematurity which is a common condition in the neonatal period caused by immature brainstem respiratory neural output may result in intermittent hypoxia and cause of oxidative stress during this vulnerable developmental period. Objective: To test if chronic intermittent hypoxia (CIH) alters oxidative metabolism and resultant redox status in the medulla of rat pups. Methods: Litters of 10 rat pups and their dams were assigned to: normoxia (controls) and intermittent hypoxia (Hx). Exposure occurred from P1-P7. CIH consisted of exposing rat pups to alternating cycles of N2 and air: 45 seconds of hypoxia (nadir of 5% O2 ) was administered every 5 minutes for 8 hours/day. For controls, animals were kept at air. On the eighth day, brainstems were harvested, snap-frozen in liquid nitrogen. Reduced (GSH) and oxidized (GSSG) glutathione, and precursors -glutamyl-cysteine (-G-cysteine) and L-cysteine in medulla were determined by UPLC-MS/MS and MDA in medulla was determined by HPLC. Results: GSH was significantly reduced in medulla of rat pups submitted to chronic intermittent hypoxic (CIH) episodes associated with reduction in GSH/GSSG ratio. GSH precursors were also significantly lower in the brainstem of the Hx group. Conclusions: Intermittent hypoxic episodes in rat pups cause a significant reduction in GSH and its precursors in the developing brainstem. GSH and precursors are major determinants of redox status. These alterations may activate transcription factors relevant to the expression of antioxidant enzymes and inflammation. We speculate that oxidant stress may impair central respiratory control and contribute to further enhance recurrent apnea/impaired oxygenation.